Lignin solubility in non‐imidazolium ionic liquids - Glas, Daan; Van Doorslaer, Charlie; Depuydt, Daphne; Liebner, Falk; Rosenau, Thomas; Binnemans, Koen; De Vos, Dirk E (Journal of chemical technology and biotechnology (1986), 2015)
BACKGROUND: Until now ionic liquid research concerning lignin dissolution and processing has mainly focused on the imidazolium type ionic liquids. Other types of ionic liquids can extend the scope of such processes due to their better thermal, base and oxidation stability. RESULTS: A series of ammonium, phosphonium and pyrrolidinium based ionic liquids was screened for lignin dissolution. Tributylmethylphosphonium methyl sulfate and N‐butyl‐N‐methylpyrrolidinium dicyanamide displayed the highest Kraft lignin dissolution at 90 °C, with 460 and 390 g kg‐¹, respectively. The latter ionic liquid combines this high solubility with a rather low viscosity, resulting in a promising medium for processing lignin and for other potential applications in wood separation technology. Owing to the ionic character of lignosulfonate, its solubility was even higher. The molecular structures of both recovered lignin and ionic liquid were not changed after lignin dissolution, as proven with FT‐IR, Curie‐point pyrolysis‐GC/MS and NMR. The ionic liquid could be recycled without loss in lignin dissolving ability. CONCLUSION: Ammonium, phosphonium, and pyrrolidinium based ionic liquids proved suitable for lignin dissolution, if combined with the right counterion. © 2014 Society of Chemical Industry